Educational Solutions for Children with Cerebral Palsy - Driver, Lynn; Omichinski, Donna Riccio; Miller, Nicole; Sandella, Danielle; Warschausky, Seth (Journal of the American Academy of Special Education Professionals, 2010)
This paper characterizes educational strengths and needs of children with cerebral palsy (CP) and connects research findings from the University of Michigan’s Adapted Cognitive Assessment Lab (ACAL) to current special educational requirements. It acknowledges the uniqueness of educating a child with significant motor and communication disabilities and suggests a reasonable starting point to develop an education plan for children with CP. The authors propose two key components critical to the educational success of children with CP: Accessible Assessment and Accessible Curriculum. Emphasis is placed on the importance of working within the mandated educational guidelines to best meet the individual educational needs of students with CP. Also included in the manuscript is a comprehensive appendix of resources related to the educational needs of children who receive special education services, a resource appendix specific to reading, examples of accommodations vs. modifications, and a diagram that highlights the key concepts of this article.